1997
DOI: 10.1007/3-540-63890-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic programming on distance-hereditary graphs

Abstract: Abstract. In this paper, we define a one-vertex-extension tree for a distance-hereditary graph and show how to build it. We then give a unified approach to designing efficient dynamic programming algorithms for distance-hereditary graphs based upon the one-vertex-extension tree. We give linear time algorithms for the weighted vertex cover and weighted independent domination problems and give an O(n 2) time algorithm to compute a minimum fill-in and the treewidth for a distance-hereditary graph. IntroductionThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…• Pick a target vertex x in G, add a new vertex x to G: 5 We may be applying operations in a slightly different order than given in constructing the tree. As long as we read the tree in level order, this does not change the underlying graph.…”
Section: Distance-hereditary Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Pick a target vertex x in G, add a new vertex x to G: 5 We may be applying operations in a slightly different order than given in constructing the tree. As long as we read the tree in level order, this does not change the underlying graph.…”
Section: Distance-hereditary Graphsmentioning
confidence: 99%
“…We call these trees vertex incremental trees [5], and they are structures that encode the vertex incremental operations used to construct the corresponding graphs. Historically, this idea first emerged in the enumeration of cographs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 44 showed that distancehereditary graphs can be defined, recursively. By Theorem 8.1, a distance-hereditary graph G has its own twin set TS G , the twin set TS G is a subset of vertices of G, and it is defined recursively.…”
Section: Distance-hereditary Graphsmentioning
confidence: 99%
“…The other nodes have margin 0, and the other arcs have distribution 0. Hence the graph in Figure 5 has a Hamiltonian cycle, e.g., (1,8,2,9,3,10,4,11,5,14,16,15,7,12,6,13,1).…”
Section: The Hamiltonian Cycle Problemmentioning
confidence: 99%
“…Especially, Bandelt and Mulder showed that any distance hereditary graph can be obtained from K 2 by a sequence of extensions called "adding a pendant vertex" and "splitting a vertex." Using the characterizations, many efficient algorithms have been found for distance hereditary graphs [6,2,5,21,17,7]. However, the recognition of distance hereditary graphs in linear time is not so simple; Hammer and Maffray's algorithm [14] fails in some cases, and Damiand, Habib, and Paul's algorithm [9] requires to build a cotree in linear time (see [9,Chapter 4] for further details), where the cotree can be constructed in linear time by using recent algorithm based on multisweep LBFS approach by Bretscher, Corneil, Habib, and Paul [4].…”
Section: Introductionmentioning
confidence: 99%